Two new species of Lachesilla of Pedicularia group (Psocodea: ‘Psocoptera’), from Valle del Cauca, Colombia - García Aldrete, Alfonso Neri; González Obando, Ranulfo; Saldaña, Cinthya (Revista Colombiana de Entomología, 2013)
Two new species of Lachesilla, in species group Pedicularia, from Valle del Cauca, Colombia, are here described and illustrated. The males of these species present one mid clunial apophysis directed posteriorly. Species in group Pedicularia, in which the males have one mid clunial apophysis were previously known from the Departments of Cuzco and Madre de Dios, Peru. Males of Lachesilla with one mid clunial apophysis are known only in the Chinese Ceratolachesillus quinquecornus Li, and in the Mexican L. cerorma García Aldrete, in the latter, the clunial apophysis bears abundant setae, quite distinct from the glabrous, sclerotized apophyses of the other species.